Analisis Hubungan Volatilitas Pasar Saham, Foreign Portfolio Investment, Dan Indikator Makroekonomi Pada Saham Syariah Sektor Energi Di Indonesia Tahun 2011-2023 - Ibrohim, Syahrul 'Ali (UI Scholars Hub, 2024)
This research aims to analyze the relationship between stock market volatility, Foreign Portfolio Investment (FPI), interest rates, exchange rates, and the Industrial Production Index (IPI) on Islamic stocks in the energy sector in Indonesia from 2011 to 2023, using the Autoregressive Distributed Lag (ARDL) method and monthly frequency data. The research results indicate the existence of cointegration or a long-term relationship among each tested variable as the dependent variable. The long-term test results show that volatility in Islamic stocks in the energy sector is positively influenced by FPI activity. Furthermore, the exchange rate positively affects the IPI. Meanwhile, in the short term, FPI activity is negatively influenced by the FPI value of the previous period. On the other hand, stock market volatility positively affects FPI. Additionally, the IPI is positively influenced by the IPI value of the previous 3 months, the exchange rate, FPI activity, as well as stock market volatility up to 1 month prior.